Mediation Of Organizational Commitment Between Discipline And Human Resource Development In Improving The Performance Of Local Government Employees In Pandeglang District - Febratama, Dava; Basrowi; Sariwardani, RR. Andriani (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This research is motivated by the importance of improving the performance of civil servants within the Pandeglang Regency Government in facing the increasingly complex dynamics of public service delivery. Discipline and human resource (HR) development are seen as strategic keys to boosting productivity, while organizational commitment is believed to strengthen employee engagement with the organization. The purpose of this study is to analyze the influence of discipline and human resource development on employee performance, and to test the role of organizational commitment as a mediating variable. The methodology used is a quantitative approach with the method Structural Equation Modelling-Partial Least Squares (SEM-PLS). Data was collected through the distribution of questionnaires to 297 civil servants which are selected using techniques proportionate stratified random sampling, so that it can represent conditions proportionally in each work unit. The results of the study indicate that discipline has a positive and significant effect on employee performance, both directly and indirectly through organizational commitment. Human resource development has a positive effect on organizational commitment, but does not have a significant direct effect on employee performance. These findings indicate that organizational commitment acts as an important mediator, strengthening the relationship between discipline and performance, as well as between human resource development and employee performance. The conclusion of this study confirms that improving employee performance in the Pandeglang Regency Regional Government does not only depend on efforts to improve discipline and develop HR capacity, but also requires strengthening organizational commitment as a binding factor that ensures the sustainability of results. Further discussion implied the need for an integrated civil service management strategy, such as implementing a culture of discipline based on exemplary behavior, sustainable competency development programs, and internal policies that strengthen employee loyalty and commitment to the organization. These efforts are expected to improve the quality of public services that are responsive, accountable, and oriented toward public satisfaction.